Double-sided photonic crystal fiber (PCF) temperature and refractive index (RI) sensor based on surface plasmon resonance (SPR). Issue 1 (2nd January 2023) - Wang, Jia-Kai; Ying, Yu; Gao, Zhi-jun; Xu, Ke; Qi, Qi; Si, Guang-yuan
Abstract: A double-sided photonic crystal fiber (PCF) temperature and refractive index (RI) sensor based on surface plasmon resonance (SPR) is reported to simultaneously measure temperature and RI. An arc groove covered with gold is filled with chloroform for temperature detection. The D-shaped plane coated with silver is in direct contact with the analyte to provide the RI. Two independent channels distinguish temperature and RI changes, thus completely solving the cross-sensitivity problem. The sensing characteristics of the plane coating, arc coating, and inner ring coating are discussed. The influence of gold film closure on the optimum RI measurement range was identified, and the best sensing structure of chloroform as a temperature-sensitive material is obtained. The sensing characteristics of different types of metal films are investigated. It is concluded that the band separation may be achieved by plating gold film and silver film in the arc groove and D-plane, respectively. The influence of the central angle of the arc groove on the sensor characteristics was investigated. High-order resonance may be avoided at a 180° center angle. The influence of the thickness of the metal film on the sensitivity of the sensor is studied numerically, and the optimal coating thickness is 50 nm. This work simplifies the selection of the RI range of sensing materials and provides a new approach to solve the high-order resonance and band interference in SPR multi-parameter sensors.